(untitled) (MAUSAM, 1982)
Delhi exhibited several small warm pockets due to agglomeration of houses in 30. colonies interspersed by green vegetation, open areas, wide roads, parks and maidans etc. Two peaks of heat island intensity were observed -one in the early night and another in the early morning. The early morning heat island is stronger than the early night. Humidity islands exhibited inverse relation to heat islands wherever moisture is not available but followed heat islands in intensity where moisture is available. Humidity islands also exhibited two peaks similar to heat islands. The early morning peak was in phase with heat island but the early night peak is out of phase. The thermal radiant emittance from different surfaces in Delhi like green areas, concrete roads, tar roads, built-up areas are found to be responsible for the formation of several warm pockets instead of a single intense heat island.